Robust fault tolerant tracking controller design for vehicle dynamics: A descriptor approach. (September 2015) - Aouaouda, S.; Chadli, M.; Boukhnifer, M.; Karimi, H.R.
Abstract: In this paper, an active Fault Tolerant Tracking Controller (FTTC) scheme dedicated to vehicle dynamics system is proposed. To address the challenging problem, an uncertain dynamic model of the vehicle is firstly developed, by considering the lateral forces nonlinearities as a Takagi–Sugeno (TS) representation, the sideslip angle as unmeasurable premise variables and the road bank angle as an unknown input. Subsequently, the vehicle dynamic states with the sensor faults are jointly estimated by a descriptor observer on the basis of the roll rate and the steering angle measures. Then a fault tolerant tracking controller is synthesized and solutions are proposed in terms of Linear Matrix Inequalities (LMIs). Simulation results show that the proposed FT control approach can effectively improve tracking performance of the vehicle motion.